- 1-214-256-5804
- info@tutorpace.com

11(x – 1) + 6 if x = 2?

Here the unknown variable which needs to be solved for is x.

First step: Distribute 11 for x - 1.

This gives: (11 x – 11) + 6 = 11 x – 11 + 5 = 11 x - 6.

Now substituting x = 3 in the simplified equation 11 x – 6.

This reduces the given equation to 11 (3) – 6 = 33 - 6 = 27.

Hence the solution is x = 27.

Here the variable is x; distributing the number in front of the braces.

This gives 5 (x - 4) = 5 x – 20; 2 (x + 3) = 2 x + 6.

Combining the similar terms in the equation.

This gives 5 x – 20 + 2 x + 6 - 30 = 7 x – 44.

Hence the simplified form of the equation is 7 x - 44.